Domestic servants in households in sub-Saharan Africa : an attempt of measure and analyse - (:unkn) unknown (My University, 2019)
While domestic work in Africa carried out by people outside from the family requires increasing interest, there is a lack of adequate data to measure its extent and analyse its characteristics. The article provides a critical inventory of data sources for capturing domestic situations. Based on the available data, it synthesizes and compares the prevalence levels of the phenomenon between countries, but limited to domestic workers hosted by their employing household, with a more in-depth comparative analysis between Bamako and Dakar.
Keywords: African Research